EKSTRAKSI ABU KAYU DENGAN PELARUT AIR MENGGUNAKAN SISTEM BERTAHAP BANYAK BERALIRAN SILANG - Santosa, Imam; Sulistiawati, Endah (CHEMICA: Jurnal Teknik Kimia, 2014)
As an agricultural country, Indonesia has natural resources are very abundant , one of which is wood . Wood ash from household and industrial waste has not been used , whereas according to Pitman high potassium content . The solubility of potassium carbonate in high water , so effective when extracted with water . However, high humidity in Indonesia drying wood for fuel so low that allegedly affect the quality of the ash obtained . In this research, the extraction of wood ashes with water using a solvent system gradually many wing cross .The experimental study was conducted in a university laboratory Ahmad Dahlan , Yogyakarta . The procedure used is the extraction of wood ash 200 , 300 and 400 grams with 1000 ml of solvent water for 5 minutes using a glass beaker , filtering with the aid of a vacuum pump , and acidi alkalimetri analysis using 0.1 N HCl residual solids by filtration and then in water kontakkan again and so do the same thing 5 times . Raw materials derived from wood ash combustion for drying of the wood cutting industry and water used in the form aquadestilata .Extract wood ash derived from the combustion for drying small normality sawmill industry . The results of the analysis can be made curve that describes the operating line and curve logarithmic form of the equation of equilibrium in the form of linear equations . Moreover, it can be made a graph illustrating a series of 5 stages of operation which is a combination of single phased extraction .